The influence of acculturation on endocrine reactivity during acute stress in urban black males - Malan, N.T.; Brits, J.S.; Eloff, F.C.; Huisman, H.W.; Kruger, A.; Laubscher, P.J.; Pretorius, P.J.; Steyn, H.S. (Stress medicine, 1996)
Urbanization is a world‐wide phenomenon and results in a radical and sometimes total change in living conditions. This process is accompanied by a significant increase in the incidence of western‐type diseases virtually unknown in traditional rural communities. Especially in a multicultural society like South Africa, rural people moving to the city will experience cultural shock leading in many cases to a large degree of acculturation. In this study the effect of acculturation on endocrine reactivity was studied in a population of Tswanas. It was found that significant differences in endocrine reactivity exist not only between rural Tswanas and urban whites but in some instances also between rural Tswanas and urban Tswanas. During the cold pressor test, the testosterone reactivity and to a lesser extent the prolactin reactivity of the urban Tswanas tended to approach that of the white group as a function of their level of acculturation. All the Tswana groups had a significantly higher plasma renin activity during acute stress than the whites, which could have a bearing on the tendency of urban blacks to develop hypertension.